Utilization of Decapterus russelli in fish cakes and surimi - Yu, Swee Yean (John Wiley & Sons, 1993)
Decapterus russelli was substituted for Nemipterus tolu in the manufacture of fish cake. There were no significant differences in colour and odour for up to 80% substitution with D. russelli but flavour, texture and overall acceptability were adversely affected. Formulations using 60% D. russelli were acceptable to sensory panellists. D. russelli surimi was stored at - 200e for 5 months without detrimental changes in colour, TBA value, hardness and elasticity and salt-soluble proteins.